Development of the Ethnochemistry Magazine Using Traditional Gold Mining Culture and Gold Crafts - I Nyoman Loka; Jeckson Siahaan; Muntari Muntari; Baiq Fara Dwirani Sofia; Syarifa Wahidah Al Idrus; Baiq Royatul Aeni (Jurnal Pijar MIPA, 2025)
Research and development were conducted with the aim of describing the chemistry concepts contained in the traditional gold mining culture in Prabu village, Middle Lombok and gold crafts in Sekarbela, Mataram. This research is a qualitative descriptive study with a survey approach, conducted in collaboration with 4D Research and Development. The data in this study were collected using the triangulation method, which included interviews, observations, and literature studies. The data analysis technique employed the Miles and Huberman method, which involved data reduction, data presentation, and drawing conclusions. The results of the study indicate that in the traditional gold mining culture in Prabu Village, Middle Lombok, and the gold craft cultural activities in Sekarbela Mataram, there are chemical concepts, including elemental chemistry, reaction equations, oxidation-reduction reactions, the application of the solubility product of salts to separate chemical components from their mixtures, the concept of acids and bases, and the concept of colloids. Teaching materials in the form of ethnochemistry magazines from research and development have a feasibility category that is very feasible, based on the magazine's size, cover design, and content design, with an average V coefficient of 0.94. The feasibility of ethnochemistry magazines, based on the material component indicator, with sub-indicators of material suitability and stimulating curiosity, as well as the feasibility of presentation, with sub-indicators of presentation techniques and presentation support, and the linguistic component indicator, is classified as very feasible, with an average V coefficient of 0.93. In general, ethnochemistry magazines from research and development are classified as very feasible, with an average V coefficient of all aspects of 0.935.